Identifikasi dan Analisis Faktor Internal dan Eksternal pada UMKM Konveksi Reihan Menggunakan Metode Analisa SWOT dan QSPM - Lorenzo Andreas; Uun Novalia Harahap; Denny Walady Utama (CV. IRA PUBLISHING, 2023)
Micro, small, and medium enterprises (MSMEs) Reihan Convection is a home industry company manufacturing bags. This company is still experiencing problems in increasing bag sales. This research aims to formulate a business development strategy so that companies can consider it to increase bag sales. This study uses the SWOT and QSPM methods. The SWOT method is used to determine strategy, while the QSPM method is used to specify alternative techniques used by the company at this time. The research results were obtained for SO strategy focused on product development, ST concentrating on maintaining and improving product and workforce quality, WO establishing solid partnerships with related parties, and WT concentrating on practical and targeted promotions. The alternative strategies obtained are Product Development (TAS = 6.350), Integration strategy (TAS = 6.290), and Intensive strategy (TAS = 5.761).